Improvement Of Knowledge About Range Of Motion (ROM) In Elderly Caregivers - Siti Robeatul Adawiyah; Setiyarto, Setiyarto; Dian Anggraini; Ely Triyana; Ahmad Arif (Jurnal EduHealth, 2025)
Range of Motion (ROM) exercises are essential for elderly individuals with joint limitations, particularly in nursing homes where many residents experience joint stiffness. Caregivers, responsible for assisting these elderly individuals, often lack knowledge of ROM exercises, which are crucial in alleviating joint issues and preventing muscle and tissue degeneration. This study aims to ensure that elderly caregivers comprehend and can correctly teach ROM techniques, as well as understand their benefits for elderly individuals with physical mobility limitations. Additionally, caregivers should be able to implement ROM procedures and conduct evaluations to maximize the benefits for the elderly. This study uses a quantitative method with a pre-experimental approach to measure changes in caregivers’ knowledge after receiving ROM training. Data were collected using pre-test and post-test questionnaires, assessing caregivers’ understanding of ROM techniques and their benefits for the elderly. Observations were also conducted during the training to evaluate participant engagement. The data from the pre-test and post-test were analyzed using descriptive statistics, with frequency analysis to measure knowledge changes such as 30%, 20%, or 10% improvements, and identifying those with no improvement or decreased knowledge. The results show that The Training of Trainee (TOT) activity successfully improved caregivers’ knowledge. Among the 20 participants, 7 (35%) showed a 20% increase in knowledge, 4 (20%) showed a 10% improvement, and 1 (5%) had a 30% increase. However, 4 participants (20%) showed no improvement, and 4 (20%) exhibited a decrease in knowledge. Despite some negative outcomes, the overall result indicates that the training effectively enhanced caregivers’ understanding of ROM exercises and their role in improving the mobility of elderly individuals. The TOT activity successfully achieved its goal of enhancing the caregivers' knowledge of ROM techniques. The results suggest that further training is necessary to ensure continuous improvement in caregivers' skills, ultimately benefiting the physical mobility of elderly individuals.